ASTROPOLITIK: TEKNOLOGI, MILITERISASI DAN PEPERANGAN ANTARIKSA - Muhammad Erza Pradana (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2022)
This article aims to add to the current literature on astropolitics in the field of International Relations. Space has long been regarded as the new frontier of human domination. This is then realized when space technology advances, allowing humans to conduct space programs. The Soviet Union's Vostok I program and Sputnik I marked the beginning of space technology development. The United States soon expanded their space program which resulted in the landing of the first 2 humans on the Moon. We can see that the utilization of space cannot be separated from political activity since the inception of the human space program. Furthermore, the space program is inextricably linked to military activies. Since the Cold War, countries have been competing for space domination. Despite the fact that the cold war has been long over, the rivalry for space domination between countries has resumed. The militarization and development of space weaponry gave rise to the idea that a space war between states was becoming a real possibility. Keywords: Astropolitics, space technology, space militarization, space security, space warfare